Systematic Review and Meta-Analysis of Integrated Studies on Salmonella and Campylobacter Prevalence, Serovar, and Phenotyping and Genetic of Antimicrobial Resistance in the Middle East-A One Health Perspective - Said Abukhattab; Haneen Taweel; Arein Awad; Lisa Crump; Pascale Vonaesch; Jakob Zinsstag; Jan Hattendorf; Niveen M. E. Abu-Rmeileh (MDPI AG, 2022)
Background:Campylobacter and Salmonella are the leading causes of foodborne diseases worldwide. Recently, antimicrobial resistance (AMR) has become one of the most critical challenges for public health and food safety. To investigate and detect infections commonly transmitted from animals, food, and the environment to humans, a surveillance-response system integrating human and animal health, the environment, and food production components (iSRS), called a One Health approach, would be optimal. Objective: We aimed to identify existing integrated One Health studies on foodborne illnesses in the Middle East and to determine the prevalence, serovars, and antimicrobial resistance phenotypes and genotypes of Salmonella and Campylobacter strains among humans and food-producing animals. Methods: The databases Web of Science, Scopus, and PubMed were searched for literature published from January 2010 until September 2021. Studies meeting inclusion criteria were included and assessed for risk of bias. To assess the temporal and spatial relationship between resistant strains from humans and animals, a statistical random-effects model meta-analysis was performed. Results: 41 out of 1610 studies that investigated Campylobacter and non-typhoid Salmonella (NTS) in the Middle East were included. The NTS prevalence rates among human and food-producing animals were 9% and 13%, respectively. The Campylobacter prevalence rates were 22% in humans and 30% in food-producing animals. The most-reported NTS serovars were Salmonella Enteritidis and Salmonella Typhimurium, while Campylobacter jejuni and Campylobacter coli were the most prevalent species of Campylobacter. NTS isolates were highly resistant to erythromycin, amoxicillin, tetracycline, and ampicillin. C. jejuni isolates showed high resistance against amoxicillin, trimethoprim-sulfamethoxazole, nalidixic acid, azithromycin, chloramphenicol, ampicillin, tetracycline, and ciprofloxacin. The most prevalent Antimicrobial Resistance Genes (ARGs) in isolates from humans included tetO (85%), Class 1 Integrons (81%), blaOXA-61 (53%), and cmeB (51%), whereas in food-producing animals, the genes were tetO (77%), Class 1 integrons (69%), blaOXA-61 (35%), and cmeB (35%). The One Health approach was not rigorously applied in the Middle East countries. Furthermore, there was an uneven distribution in the reported data between the countries. Conclusion: More studies using a simultaneous approach targeting human, animal health, the environment, and food production components along with a solid epidemiological study design are needed to better understand the drivers for the emergence and spread of foodborne pathogens and AMR in the Middle East.